PRODUK MEDIA DALAM PEMBELAJARAN SASTRA: PENGKAJIAN SEJARAH DAN LEGITIMASI KEKUASAAN DALAM NOVEL ADBM DAN NSSI KARYA S.H MINTARDJA - Sugiri, Drajat (Universitas Negeri Surabaya, 2017)
Hegemony is often used in political science to show the meaning of domination, but through the study of the novel, it can be seen hegemony opposed to domination in power at that time is determined by physical force. Through the novel Fire in Bukit Menoreh (ADBM) and Nagasasra Inten belt can be seen that both were created for a legitimacy and hegemony. In addition to using chronicle, through ADBM legitimizing the power of Demak-ranging search and the loss of a dagger kingdom Nagasasra Belt Inten through figures Mahesa jenar (Rangga Tohdjaya), while through NSSI solidified the power of Mataram although indirectly, but can be determined based depiction of a central Raden Danang Sutawijaya and Ki Gedhe natural Pemanahan Mentaok development board that turns into Mataram. On the other side of the central figures like Supreme Sedayu fictitious, Swandaru and Kiai Gringsing strengthen the position of both. Analyzing can be used through the theory of semiotics, in it presents a reading method is heuristic and hermeneutic can find links hegemony and legitimacy that is displayed by the characters, storyline, background story and other elements